A HUMANIZAÇÃO NO CUIDADO A PESSOAS EM SITUAÇÃO DE RUA: RELATO DE EXPERIÊNCIA NO PROJETO AGASALHO (CIPEEX, 2026)
Introduction: The humanization of healthcare is essential in Nursing, considering the patient in their entirety and promoting dignity, empathy, and sensitivity to social vulnerabilities. Homeless individuals face barriers to accessing healthcare, food, and hygiene services, requiring ethical and comprehensive attention from professionals. Objective: To describe the experience of Nursing students in the extension activity entitled “Projeto Agasalho”, addressing the application of humanization practices in the care of homeless people. Methodology: This is an experience report of an extension activity linked to the course Health Psychology, carried out in the first semester of 2025, structured according to the theoretical framework of Maguerez’s Arch. Results and Discussion: The students had direct contact with homeless individuals, practicing active listening, empathy, dialogue, and teamwork. The experience enabled the integration of theoretical knowledge with practice, the application of principles of humanized care, and the understanding of the social and emotional dimensions of the assisted population. The activity promoted ethical and social reflection, emotionally impacting the students and reinforcing Nursing’s role in reducing inequalities. Conclusion: The experience contributed to the development of technical, socioemotional, and ethical competencies, consolidating the importance of humanization in the care of vulnerable populations and highlighting the relevance of university extension as a tool for integrating theory and practice.Keywords: Humanization; Homeless people; University extension; Nursing.
Keywords: Humanização; Pessoas em situação de rua; Extensão Universitaria; Enfermagem